Art Now '87. - Art Now '87 (Kobe : The Hyogo Prefectural Museum of Modern Art - The Asahi Shimbun, 1987)
Inagaki, Atsuo ; Otsuka, Yumiko ; Katayama, Masahito ; Kawashima, Keijyu ; Fitzgerald, Simon Paul ; Satö, Tomoko ; Shibano, Yukihito ; Tashima, Etsuko ; Tanaka, Miwa ; Tanaka, Youko ; Tsuda, Teruyoshi ; Tsutsumi, Nobuko ; Tsuzuki, Fusako ; Nagano, Hisato ; Matsuo, Naoki ; Yamaguchi, Kazumi ; Ono, Kazunori ; Kikuchi, Takashi ; Michikita, Eiji
Art Now '87, The Hyogo Prefectural Museum of Modern Art, Kobe, 1987.2.28 - 3.22
English-Japanese
kunstcatalogus